1999
DOI: 10.1017/s0022112099004851
|View full text |Cite
|
Sign up to set email alerts
|

Can the atmospheric kinetic energy spectrum be explained by two-dimensional turbulence?

Abstract: The statistical features of turbulence can be studied either through spectral quantities, such as the kinetic energy spectrum, or through structure functions, which are statistical moments of the difference between velocities at two points separated by a variable distance. In this paper structure function relations for two-dimensional turbulence are derived and compared with calculations based on wind data from 5754 airplane flights, reported in the MOZAIC data set. For the third-order structure function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
366
1
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(422 citation statements)
references
References 26 publications
(55 reference statements)
48
366
1
7
Order By: Relevance
“…Using these hypotheses, a careful analysis along the lines of [10,28,30] justifies in the range ℓ ≪ r ≪ L, the expansion…”
mentioning
confidence: 99%
“…Using these hypotheses, a careful analysis along the lines of [10,28,30] justifies in the range ℓ ≪ r ≪ L, the expansion…”
mentioning
confidence: 99%
“…Fortunately, for many atmospheric conditions (Gage, 1979;Nastrom and Gage, 1985;Lindborg, 1999;Wikle et al, 1999;Cho and Lindborg, 2001;Lindborg and Cho, 2001;Lenschow and Sun, 2007;Riley and Lindborg, 2008) there is a robust scaling of turbulence in the horizontal plane that connects the resolved scales of the NWP models to the subgrid scale turbulence statistics. More work is required to extend these results to other atmospheric conditions, such as the night-time residual layer and stable boundary layers.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…An example is shown in Figure 1 for the Global Forecast System (GFS) model at 250 hPa pressure altitude and a latitude band of 40 • -50 • N over CONUS, which provides the best match to the high-density ACARS aircraft data over the same domain (note that past results (Lindborg, 1999) are based on unknown averaging domains which have similar scaling laws). There is excellent agreement between the predictions of the effective square filter with L = 150 km and the GFS average structure function, even though the GFS grid is not exactly square.…”
Section: Statistical Description Of the Atmosphere And The Definitionmentioning
confidence: 99%
“…Random medium condition in Equation (3) assumes that the randomness intensity, B, is low enough such that the medium has a quite small number of particles, which leads to having large separations, ρ, among particles. In [22], it was demonstrated that D agrees better with the two-dimensional isotropic relation for wider ρ among particles than for narrower ρ. It was deduced that a random medium can be assumed as a two-dimensional turbulence in the enstrophy inertial range.…”
Section: Scattering Problemmentioning
confidence: 98%